On Regular Semi Supra Open set and Regular Semi Supra Continuity - Marwa Fathi Ahmed; Taha H. Jasim (Tikrit Journal of Pure Science, 2022)
The aim of this paper is to present the concepts of -supra continuous function, -semi supra continuous function, -regular open set and -regular semi supra open set in -supra topological space. We studied relations between these functions and check up from some of its characteristics.